Gung Ho - Ron Howard; Watanabe, Gedde; George Wendt; John Turturro; Mimi Rogers; Sab Shimono; Sô Yamamura; Michael Keaton (USA Paramount Pictures, 1986)
Hunt Stevenson works for a large car manufacturer that has just been bought out by a Japanese firm. Suddenly finding himself having to justify his own job, he's forced to choose between redundancy or the seemingly inhuman Japanese work ethic that the new owners have brought with them.
When a Japanese car company buys an American plant, the American liason must mediate the clash of work attitudes between the foreign management and native labor.
Edwin Blum
Languages : English, German, French, Spanish, Italian Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Swedish, Arabic, Bulgarian, Hebrew
Keywords: Drama; Comedy